Pengaruh Kualitas Makanan dan Komunikasi Terhadap Kepuasan Pelanggan di Warung Dedalu Kerobokan Bali - Ni Putu Lovi Agustiari; Desak Made Purnama Dewi; Anak Agung Ratih Wijayanti (Universitas Triatma Mulya, 2026)
This study aims to determine and analyze the effect of food quality and communication, both partially and simultaneously, on customer satisfaction at Warung Dedalu, Kerobokan, Bali. The research was motivated by customer complaints regarding inconsistent food taste, incorrect orders, and service delays caused by ineffective communication between employees and with guests. This research uses a quantitative approach with survey methods. Data were collected through questionnaires distributed to 100 customers as respondents. Data analysis employed multiple linear regression, statistical descriptive, instrument testing, and classical assumption tests. The results showed that partially, food quality and communication had a positive and significant effect on customer satisfaction. Simultaneously, both variables also had a significant effect. Communication was found to be more dominant than food quality. The findings suggest improving communication training and maintaining consistent food quality to enhance customer satisfaction and loyalty.